Phytochemicals and Antioxidant Activity of Citrus Seed Oils - Malacrida, Cassia Roberta [UNESP]; Kimura, Mieko [UNESP]; Jorge, Neuza [UNESP] (Karger, 2012)
Citrus seeds represent substantial wastes of citrus-processing. Oils extracted from orange (Citrus sinensis), lemon (Citrus limon) and tangerine (Citrus reticulata) seeds were investigated. The seeds were removed from the fruits, washed, dried at room temperature, ground and the oils extracted using a Soxhlet extractor. The seed oils were analyzed in terms of the lipid content, fatty acid, tocopherol and carotenoid compositions, total phenolic content, oxidative stability and the radical-scavenging activity. The oil content of citrus seeds ranged from 34.92 to 41.66%. The oils showed high degrees of unsaturation and essential fatty acids. Oils exhibited also natural antioxidants specially tocopherols and phenolic compounds. Oxidative stability and antioxidant activity were influenced by unsaturated fatty acids and tocopherol contents in the analyzed oils.
Keywords: orange; lemon; tangerine; fatty acid; Antioxidants